THE NORTHERN CAUCASUS: THE STATEHOOD ISSUE AS TREATED BY THE NATIONAL, ISLAMIC, AND POLITICAL MOVEMENTS - BABICH, Irina (CENTRAL ASIA AND THE CAUCASUS, 2005)
In the 1990s, the Northern Caucasus was swept by ideas of setting up different kinds of statehood which to a large extent determined the directions of the national, Islamic, and political movements. The problem of statehood assumed its most complicated form in Chechnia. In the early 1990s, when Islam had just resumed its former place in the Northern Caucasus, but the Muslim leaders had not yet gained political weight and had no money to speak of, national movements pushed to the fore. Judging by their leaders’ political statements, the statehood issue was one of the priorities. In Kabardino-Balkaria (KBR), for example, the law passed by the R.S.F.S.R. Supreme Soviet, On the Rehabilitation of Repressed Peoples, added impetus to the local and similar movements elsewhere in the region. The law not only stipulated that the formerly repressed peoples should receive privileges—it was a political document. The national movements in the republic developed “within the framework of restoring Kabardinian and Balkar statehood.”1 In the first half of the 1990s, the national movements still thought of the statehood issue as a national-territorial principle of state organization and so-called national-political self-identification. These were two major instruments of political struggle in the Caucasus. In 1991, the leaders and supporters of the Balkar national movement adopted a Declaration on Setting up the Republic of Balkaria and the National Sovereignty of the Balkar People, the main principles of which were formulated in the Key Provisions of the Conception of the National-State Organization and the Reform of the Political System of Kabardino-Balkaria.2 In 1992, the leaders of the Kabardinian national movement, being convinced that “the statehood of the Kabardinian people was restored in 1921,” responded with a similar decision On the Restoration of the Kabardinian Republic.3 Even though both movements spoke about the peoples’ cultural resurrection and partially implemented corresponding programs,4 they were political movements first and foremost.